AN INVESTIGATION INTO THE GAP BETWEEN KOREAN UNIVERSITY STUDENTS’ GRAMMATICAL AWARENESS AND PERCEPTION - Han, Kyung-Im; Kim, Hyekyeng (Indonesian Journal of Applied Linguistics, 2017)
Despite the consistent emphasis on grammar instruction in English classrooms in South Korea, studies regarding grammar instruction have not yet been extensively conducted. The present study aims to discover the gap between learners’ grammatical awareness and their perception of major grammatical items. A total of 60 EFL learners from two local universities in South Korea participated in the study and were divided into two groups, a high-level and a low-level group. A set of tests was utilized to examine learners’ grammatical awareness and their perception of six major grammatical items—tense, prepositions, articles, voices, morphology, and vocabulary. The results demonstrated that there was a significant difference in the scores of tense, article, and voice for grammatical awareness between the high-level and the low-level group. Also, both groups scored high for the category of voice while they received low scores for vocabulary and morphology. In addition, they showed a significant difference in the scores for the perceived difficulty of articles and voice. The high-level group perceived voice as the most difficult, whereas the low-level group perceived articles as the most difficult. These findings demonstrate a gap between the learners’ grammar awareness and perception and highlight a need to design an individualized curriculum for the effectiveness of teaching as well as self-initiated studying.